PENGARUH SIKAP, NORMA SUBJEKTIF, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA SUKA SALAD SIDOARJO - Margie, Maryam Wiyar; Sari, Dewi Komala; Indayani, Lilik (Universitas Nusa Cendana, 2024)
This research was conducted to analyze the influence of attitudes, subjective norms, and brand image on purchasing decisions at Suka Salad Sidoarjo. This research uses quantitative methods using multiple linear regression testing and using the Statistical Program for Social Science (SPSS) version 25 application. The data source in the research is all Suka Salad consumers in Sidoarjo. The sampling technique in the research uses a non-probability sampling method with an accidental sampling technique. The research results show that Attitude influences Purchasing Decisions at the Suka Salad Sidoarjo restaurant, Subjective Norms have an influence on Purchasing Decisions at the Suka Salad Sidoarjo restaurant, and Brand Image has an influence on Purchasing Decisions at the Suka Salad Sidoarjo restaurant. By understanding consumer behavior regarding purchasing decisions for healthy food products, this research has the potential to support sustainable economic growth and encourage wiser consumption behavior in purchasing food products. Keywords: Attitude; Subjective Norm; Brand Image; Purchase Decision